How have inflation dynamics changed over time? Evidence from the euro area and USA - Sami Oinonen; Maritta Paloviita; Lauri Vilmi (Bank of Finland, 2013)
This paper analyzes euro area and U.S. inflation dynamics since the beginning of the 1990s by estimating New Keynesian hybrid Phillips curves with time-varying parameters. We measure inflation expectations by subjective forecasts from Consensus Economics survey and so do not assume rational expectations. Both rolling regressions and state-space models are employed. The results indicate that in both economic areas the inflation dynamics have steadily become more forward-looking over time. We also provide evidence that the impact of the output gap on inflation has increased in recent years. Overall, diminished inflation persistence emphasizes the role of credible monetary policy in inflation dynamics.
URN:NBN:fi:bof-20140807354
Keywords: E31; C22; C51; 330; inflation; Phillips curve; time-varying parameters; survey expectations